2009
DOI: 10.1177/1059840509333788
|View full text |Cite
|
Sign up to set email alerts
|

Weight Perception and Dieting Behavior Among Korean Adolescents

Abstract: This study examines relationships among weight status, weight perceptions, and dieting behaviors in South Korean adolescents. As perceptions of an ideal body for teens in Korea have changed over time, it is important for school nurses to understand these relationships to help students achieve health. A cross-sectional survey of 3,191 8th and 2,252 11th-grade students from 21 middle and high schools across Korea completed a self-administered questionnaire. The prevalence of overweight among adolescents was 17.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 23 publications
3
44
1
1
Order By: Relevance
“…A previous Korean study conducted among 8th (14 years of age) and 11th (17 years of age) grade students reported a high prevalence of weight overestimation in girls and a high prevalence of weight underestimation in boys (12% of boys vs. 24% of girls overestimated their weight, while 28% of boys vs. 10% of girls underestimated their weight). The results of this study, in regards to the relationship between gender difference and weight misperception [16], are consistent with our results. Similar results were reported from a Dutch study that revealed 37.6% weight overestimation and 11.2% weight underestimation among girls [21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A previous Korean study conducted among 8th (14 years of age) and 11th (17 years of age) grade students reported a high prevalence of weight overestimation in girls and a high prevalence of weight underestimation in boys (12% of boys vs. 24% of girls overestimated their weight, while 28% of boys vs. 10% of girls underestimated their weight). The results of this study, in regards to the relationship between gender difference and weight misperception [16], are consistent with our results. Similar results were reported from a Dutch study that revealed 37.6% weight overestimation and 11.2% weight underestimation among girls [21].…”
Section: Discussionsupporting
confidence: 92%
“…: parents' awareness of their children being overweight [9], peer weight norms [4], and public sentiments regarding ideal body size [6]. For example, the incidence of weight overestimation was higher among female Asian adolescents [7,11,16,17], whereas Asian-American girls were more likely to underestimate their weights when compared with Caucasian female adolescents in the U.S.. [7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,12,31 Our study also revealed a relationship between overweight self-perception—regardless of the accuracy of that perception—and weight loss goals. The association of weight perception and weight control behaviors has previously been seen among adolescents in other Asian regions 32,33 as well as in college age females in the United States. 15 A study in Hong Kong found no association between actual overweight status and weight control behaviors, but rather, a relationship between overweight perception and weight control behaviors.…”
Section: Discussionmentioning
confidence: 80%
“…Boys are therefore a more vulnerable group regarding metabolic outcomes, which may then lead to high risk of heart disease and other chronic diseases in adulthood. Additionally, Korean boys underestimated their weight [40]; therefore, we should help them to achieve a healthy body weight.…”
Section: Discussionmentioning
confidence: 99%